Climate Physical Risk and Asian Stock Market Returns - Marina Albanese; Guglielmo Maria Caporale; Ida Colella; Nicola Spagnolo (CESifo GmbH, 2024)
This study provides new evidence on the impact of climate physical risk (as measured by the Global Climate Risk Index (CRI) from Germanwatch) on stock market returns. Specifically, a panel model with fixed effects is estimated using annual data from 2007 to 2021 for a set of 65 countries as well as for a subset of 18 Asian ones, which are also divided in two clusters on the basis of their degree of market capitalisation. The results suggest a negative impact of climate physical risk on stock markets; this effect is more pronounced in Asian countries with lower market capitalisation, which are perceived as riskier.
Keywords: C33; G12; G18; 330; climate change; physical risk; Global Climate Risk Index; stock markets; Asia; panel data; fixed effects